2022
DOI: 10.3390/ijerph19105862
|View full text |Cite
|
Sign up to set email alerts
|

Geometric Mean Serum Cotinine Concentrations Confirm a Continued Decline in Secondhand Smoke Exposure among U.S. Nonsmokers—NHANES 2003 to 2018

Abstract: The objective of this study was to examine long-term trends in serum cotinine (COT) concentrations, as a measure of secondhand smoke (SHS) exposure, in U.S. nonsmokers using data from the National Health and Nutrition Examination Surveys (NHANES) from 2003 to 2018. We analyzed NHANES serum COT results from 8 continuous NHANES 2 year cycles from 2003 to 2018 using a liquid chromatography–tandem mass spectrometry assay that has been maintained continuously at the Centers for Disease Control and Prevention (CDC) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…However, it should be considered that the evaluation by self-report does not fully reflect exposure to actual smoking. Since 2010, changes in exposure to PS by biomarkers or cotinine concentration have not decreased significantly compared to previous years 17,34,35 , which means that the cotinine concentration in the body of non-smokers is no longer decreasing at a certain level. In particular, the issue of low-concentration PS exposure is becoming a new challenge 17 .…”
Section: Discussionmentioning
confidence: 98%
“…However, it should be considered that the evaluation by self-report does not fully reflect exposure to actual smoking. Since 2010, changes in exposure to PS by biomarkers or cotinine concentration have not decreased significantly compared to previous years 17,34,35 , which means that the cotinine concentration in the body of non-smokers is no longer decreasing at a certain level. In particular, the issue of low-concentration PS exposure is becoming a new challenge 17 .…”
Section: Discussionmentioning
confidence: 98%
“…Similarly, objective estimates of ETS exposure amongst non-smoking pregnant women would allow for more accurate and reliable tracking of temporal trends in ETS exposure. For example, recent data from eight National Health and Nutrition Examination Surveys (two-year cycles from 2003 to 2018) in the United States using serum cotinine concentrations among non-smokers as a measure of ETS showed that ETS exposure decreased by 11% every two years in all demographic groups [ 41 ]. Such longitudinal data are useful for evaluating the impact of smoke-free laws and policies on reducing ETS exposure in workplaces, public places, and homes.…”
Section: Discussionmentioning
confidence: 99%